Effectiveness of the AS04‐adjuvanted HPV‐16/18 vaccine in reducing oropharyngeal HPV infections in young females—Results from a community‐randomized trial. Issue 1 (14th December 2019) - Lehtinen, Matti; Apter, Dan; Eriksson, Tiina; Harjula, Katja; Hokkanen, Mari; Lehtinen, Tuomas; Natunen, Kari; Damaso, Silvia; Soila, Maaria; Bi, Dan; Struyf, Frank
Abstract : We studied effectiveness of the AS04‐adjuvanted HPV‐16/18 (AS04‐HPV‐16/18) vaccine against human papillomavirus (HPV) oropharyngeal infections associated with the increase of head/neck cancers in western countries. All 38, 631 resident adolescents from 1994 to 1995 birth cohorts of 33 Finnish communities were invited in this community‐randomized trial (NCT00534638). During 2008–2009, 11, 275 girls and 6, 129 boys were enrolled in three arms of 11 communities each. In Arm A, 90% of vaccinated girls/boys, and in Arm B, 90% of vaccinated girls received AS04‐HPV‐16/18 vaccine. Other Arm A/B and all Arm C vaccinated participants received control vaccine. All Arm A participants and Arm B female participants were blinded to vaccine allocation. Oropharyngeal samples were analyzed from 4, 871 18.5‐year‐old females who attended follow‐up visit 3–6 years postvaccination. HPV DNA prevalence was determined by SPF‐10 LiPA and Multiplex type‐specific PCR. Total vaccine effectiveness (VE) was defined as relative reduction of oropharyngeal HPV prevalence in pooled Arms A/B HPV‐vaccinated females vs . all Arm C females. VE against oropharyngeal HPV‐16/18, HPV‐31/45 and HPV‐31/33/45 infections were 82.4% (95% confidence intervals [CI]: 47.3–94.1), 75.3% (95%CI: 12.7–93.0) and 69.9% (95% CI: 29.6–87.1), respectively. In conclusion, the AS04‐HPV‐16/18 vaccine showed effectiveness against vaccine and nonvaccine HPV‐types oropharyngeal infections in adolescent females up to 6 years postvaccination. Abstract : What's new? The incidence of oropharyngeal cancers due to human papillomavirus (HPV) infection is increasing in Western countries. However, the efficacy of HPV vaccines against oropharyngeal infection is not well documented. Based on a large community‐randomized trial in Finland, the authors report high effectiveness (82.4%) of Cervarix vaccine against oropharyngeal HPV‐16/18 infection and moderate effectiveness against non‐vaccine types HPV‐31/33/45 infection in female adolescents. The protective effects were observed up to 6 years after vaccination. These results provide further evidence that HPV vaccination holds the potential to reduce oral HPV infection, thereby offering protection against HPV‐related head and neck cancers.